Validation of Bengali Version of Functional Digestive Disorders Quality of Life Questionnaire - Rahman , Md Mahmudur; Aftab, Hafeza (Bangladesh Journal of Medicine, 2024)
Background: Irritable bowel syndrome and Functional dyspepsia are predominant functional bowel disorders with a substantial negative impact on quality of life. Functional digestive disorders quality of life questionnaire (FDDQL) is one of the most commonly used self-administered questionnaires developed to measure health related quality of life in patients with functional bowel disorders. It has been validated in many countries, still there is no Bengali version FDDQL. This study aimed to develop a culturally adapted Bengali version of the English FDDQL and to test its reliability and validity. Methods: The English version of the FDDQL was translated into Bengali and adapted in the local socio-cultural context, following the standard recommendations by Beaton et al. published in 2000. Content validity of the adapted Bengali version was assessed by the item-level & scale level content validity indices (I-CVI & S-CVI) and Modified kappa (k*). For convergent validity, correlation between FDDQL and general health related quality of life SF-36 was assessed by Pearson’s correlation coefficients. Internal consistency was assessed using Cronbach’s alpha coefficient. The Bengali translated questionnaire was tested upon 120 patients. Results: Translation and cross-cultural adaptation procedure revealed no major deviation with the content or language. I-CVI was ³0.75, Modified kappa (k*) was ³0.67 and S-CVI was 0.91. FDDQL showed strong positive correlation (Pearson’s correlation coefficients >0.74) with SF-36. The scale demonstrated excellent internal consistency (Crohnbach’s alpha=0.86) and test-retest reliability (ICC=0.93). Conclusion: This adapted Bengali version of FDDQL is a practicable, reliable and valid instrument, and can be used for the assessment of health related quality of life in patients with functional bowel disorders. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 169-170